The role of budget emphasis and participation on budgetary slack for start up industry - Anthonius - (JAAF (Journal of Applied Accounting and Finance), 2022)
The main background of this research are the problem issues of companies in start up industry. Budgeting has been the crucial factor to be researched, related to efficiency, cost thrift, and performance improvement in start up companies. This quantitative research uses the questionnaire research instrument towards 120 startup company’s managers. The spss method were applied in data processing stage. The testing result shows that budget participation has positive impact toward budgetary slack, while budget emphasis has no impacts whatsoever. The implication of this research’s result can be utilized by startup industries as input related to Budget Participation, budget emphasis and Budgetary Slack so that the appointed budget’s target can be implemented and achieved efficiently. The originality of this research is the test related to budget emphasis, budget participation and budgetary slack in Indonesia’s startup industries.